Natural Destruction in Steven Soderbergh's Erin Brockovich - Laveliea Dinda Ramadhanty; Pratiwi Retnaningdyah (Journal of English Language Learning, 2021)
The study is to analyze natural destruction and determine the causes of thedestruction in Steven Soderbergh’s Erin Brockovich (2000). The study aims to examine how natural destruction and its causes are portrayed. The study employs an ecocritical approach toliterature to reveal apocalyptic aspects in the film and mix it with Giannetti’s cinematography theory. The result of the study reveals the issues of water pollution and drought as caused bywater exploitation by industry and the company interest for land ownership. Humans overexploit nature and it leads to a bad impact on living things.Keywords: drought, ecocriticism approach, industrial activity, natural destruction, waterpollution